2014
DOI: 10.1016/j.jebo.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Occupational sorting of school graduates: The role of economic preferences

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 53 publications
2
52
0
3
Order By: Relevance
“…The second strand of the literature presents evidence on the negative effect of risk aversion on wages (Bonin et al, 2007;Le et al, 2011). Other evidence shows that willingness to take risk is positively correlated with an individual's occupation-specific wage dispersion (Fouarge, Kriechel, & Dohmen, 2014;Pollmann et al, 2013). There is also research that shows that risk aversion is linked to wage growth (Budria, Diaz-Serrano, Ferrer-i Carbonell, & Hartog, 2013;Shaw, 1996).…”
Section: Relevant Literaturementioning
confidence: 99%
“…The second strand of the literature presents evidence on the negative effect of risk aversion on wages (Bonin et al, 2007;Le et al, 2011). Other evidence shows that willingness to take risk is positively correlated with an individual's occupation-specific wage dispersion (Fouarge, Kriechel, & Dohmen, 2014;Pollmann et al, 2013). There is also research that shows that risk aversion is linked to wage growth (Budria, Diaz-Serrano, Ferrer-i Carbonell, & Hartog, 2013;Shaw, 1996).…”
Section: Relevant Literaturementioning
confidence: 99%
“…The answers to these statements indicate how much value the individual puts on the present compared to the future. Interestingly, empirical work has shown that the CFC items are significantly correlated with conventional time preference measures (Borghans and Golsteyn, 2006;Daly et al, 2009) and predict field behaviour (Van Huizen and Plantenga, 2014;Fouarge et al, 2014). 6 Between 1996 and 2009, the DHS included the CFC items in every wave, except for the 2008 wave.…”
Section: Time Preferencesmentioning
confidence: 99%
“…Both studies emphasise the role of time preferences in the development of human capital. Other papers (e.g., Fouarge et al, 2014) assess to what extent economic preferences of recent graduates predict their occupational choice. These previous studies focus on mechanisms before entering the labour market (i.e., educational and occupational choice).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the general consensus tends to be that preferences in the domain of risk and uncertainty are stable (see e.g. Borghans et al, 2008, Sahm, 2012, and Fouarge et al, 2014, a recent study by Brachert and Hyll (2014) cast serious doubt on the stability of these preferences. Therefore, the descriptive nature of the study prevents us from drawing causal conclusions.…”
Section: Introductionmentioning
confidence: 99%